2012 9th International Conference on Electrical Engineering/Electronics, Computer, Telecommunications and Information Technolog 2012
DOI: 10.1109/ecticon.2012.6254342
|View full text |Cite
|
Sign up to set email alerts
|

Two-state peer-to-peer flow detection algorithm

Abstract: Peer-to-peer flow detection algorithm has been studied for several years. Port-based classification, regular expression, graphlet and various machine learning based algorithms have been proposed as solutions. Unfortunately, all previous algorithms have been failed in various aspects especially for the encrypted peer-to-peer traffic. In this paper, we present a new algorithm to delivers more effectiveness. We have also prototyped our algorithm and evaluate on a test-bed. The performance evaluation has demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…The data types are based on thresholds. In a previous study [9], we have found several false positives and false negatives, caused by the thresholds.…”
Section: Regular Expression (Re) Is a Packet Inspection Techniquementioning
confidence: 95%
See 4 more Smart Citations
“…The data types are based on thresholds. In a previous study [9], we have found several false positives and false negatives, caused by the thresholds.…”
Section: Regular Expression (Re) Is a Packet Inspection Techniquementioning
confidence: 95%
“…As a result, RE fails to classify peer-to-peer traffic. RE problems have been evidently shown in previous studies [3,4,7,9,11]. However, network management tools (such as ClearOS [12] and pfSense [13]) still deploy RE to classify peer-to-peer traffic.…”
Section: Regular Expression (Re) Is a Packet Inspection Techniquementioning
confidence: 97%
See 3 more Smart Citations